Posters against the Patriarchy: Violence across the Public/Private Binary in Brussels - Schoonheim, Liesbeth (HannahArendt.net, 2024)
Phenomenology has been useful in analysing the embodied dimensions of street protests (Cavarero 2021; Butler 2015; Gago 2020). However, because these analysesfocus on the gathering of bodies, little attention has been paid to the agency of inanimate objects. This paper addresses this lacuna by providing an Arendtian phenomenology of feminist street art in Brussels. Focusing on two sets of posters appearing from the late 2010s onwards, I argue for the heuristic importance of the public-private divide in mapping both the differences between and the intertwining of various forms of gender-and sexuality-based violence. Firstly, the ‘laisse les filles tranquilles’ posters provide a critical ‘stop-and-think’ moment with regard to street harassment; secondly, the posters by La Fronde allow the lamentation, denunciation, and comprehension of femicide. I conclude by arguing that because of the posters’ proximity to one another, they function as an assembly or depository (Ahmed 2016) that brings out the structural dimension of the violence inflicted under patriarchy.